Peningkatan Pengetahuan Peternak Kambing Melalui Penyuluhan Pemeliharaan Ternak di Desa Banjarwaru - Pramita, Ayu; Fadlilah, Ilma; Syafirullah, Lutfi; Tarigan, Roy Aries Permana; Ulikaryani, Ulikaryani; Sodikin, Jenal (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Many farmers Banjarwaru complain that goat growth is less than optimal, and low productivity. Based on these problems, this community service program aims to ensure that farmers understand and are able to manage goat farms according to standards independently. The method used in this community service program is to look at achievement indicators from socialization activities and cage management training and animal health recording. Based on the achievement indicators from this activity, it shows that 100% of the 20 breeders understand livestock management, housing, and the correct way to record livestock health. A total of 15 people have been able to use maintenance tools and techniques for handling diseases infected by livestock. Based on the results of the achievement indicators obtained from this service activity, it was concluded that breeders in Banjarwaru Village knew and understood the correct way to raise goats and were able to carry out maintenance activities according to good standards.